Lattice dynamics in kesterite-type Cu2ZnSnS4: Inelastic neutron scattering studies and thermoelectric properties. (March 2021) - Kandare, S.P.; Rao, Mala N.; Dahiwale, S.S.; Rao, Rekha; Dhole, S.D.; Chaplot, S.L.
Abstract: Cu2 ZnSnS4 is a p-type semiconductor that has been seen as a possible replacement for SnSe, Cu (In, Ga)Se2 etc. in thin film solar cells, due to non-toxicity and natural abundance of their constituent elements. Polycrystalline Cu2 ZnSnS4 samples (kesterite-type) were synthesized by a microwave assisted method and investigated by inelastic neutron scattering. The experimentally measured neutron-weighted phonon density of states compares reasonably well with that estimated by a computation of the lattice dynamics. These studies are then extended to elucidate the understanding of the thermal, elastic and thermoelectric properties. The lattice-dynamics calculations are able to reproduce the temperature dependence of the thermal conductivity and the thermoelectric figure of merit, as observed in experiments previously. Highlights: Investigation of kesterite-type Cu2 ZnSnS4 by inelastic neutron scattering. Neutron-weighted phonon density of states compares well with computations. Elucidation of thermal, elastic and thermoelectric properties through computations. Temperature dependence of thermal conductivity and thermoelectric figure of merit.